Aspects of the pseudo chiral magnetic effect in 2D Weyl-Dirac matter - Mizher, Ana Julia [UNESP]; Hernandez-Ortiz, Saul; Raya, Alfredo; Villavicencio, Cristian (Springer, 2018)
A connection is established between the continuum limit of the low-energy tight-binding description of graphene immersed in an in-plane magnetic field and the Chiral Magnetic Effect in Quantum Chromodynamics. A combination of mass gaps that explicitly breaks the equivalence of the Dirac cones, favoring an imbalance of pseudo-chiralities, is the essential ingredient to generate a non-dissipative electric current along the external field. Currents, number densities and condensates generated from this setup are investigated for different hierarchies of the energy scales involved.